HBR guide to managing up and across : build relationships herd cats gain influence. - Yen, Jonathan (Harvard business review guides., 2022)
ARE YOUR WORKING RELATIONSHIPS WORKING AGAINST YOU? To achieve your goals and get ahead, you need to rally people behind you and your ideas. But how do you do that when you lack formal authority? Or when you have a boss who gets in your way? Or when you're juggling others' needs at the expense of your own? By managing up, down, and across the organization. Your success depends on it, whether you're a young professional or an experienced leader. The HBR Guide to Managing Up and Across will help you: advance your agenda-and your career-with smarter networking; build relationships that bring targets and deadlines within reach; persuade decision makers to champion your initiatives; collaborate more effectively with colleagues; deal with new, challenging, or incompetent bosses; and navigate office politics.